1997
DOI: 10.1056/nejm199710093371506
|View full text |Cite
|
Sign up to set email alerts
|

The Health Care Costs of Smoking

Abstract: If people stopped smoking, there would be a savings in health care costs, but only in the short term. Eventually, smoking cessation would lead to increased health care costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
196
1
12

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(215 citation statements)
references
References 18 publications
(17 reference statements)
6
196
1
12
Order By: Relevance
“…But because non-smokers live longer, their lifetime health care costs may actually be higher. 49 Modeling these differences is analytically complex and ideologically controversial. Finally, we excluded healthrelated quality of life from the quantification of effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…But because non-smokers live longer, their lifetime health care costs may actually be higher. 49 Modeling these differences is analytically complex and ideologically controversial. Finally, we excluded healthrelated quality of life from the quantification of effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…They cost more in health care when they are alive, perhaps up to 40 per cent more (Barendregt et al 1997). A 1998 study strongly advocating legislation against tobacco usage noted that: 'The future medical costs of a young person taking up smoking today can be quite large-about $13,700 in today's (1998) dollars over the course of a lifetime' (US Office of Public Affairs 1998).…”
Section: Cigarette Smokingmentioning
confidence: 99%
“…In New Zealand, it has been shown that people over the age of 65 spend five times as much on health care than a person under 65 (Bryant et al 2004). Consequently, a number of studies have been conducted showing that smokers actually save society money (Viscusi 1999;Barendregt et al 1997). …”
Section: Cigarette Smokingmentioning
confidence: 99%
“…For instance, states then engaged in negotiations that led to the 1998 Master Settlement Agreement among 46 states, the District of Columbia, and five commonwealths and territories with the tobacco industry. Published studies on the medical costs of smoking have used a number of approaches to estimate costs, including PAR calculations (Shultz et al 1991), model-based approaches (CDC 1994;Miller et al 1998Miller et al , 1999Adams et al 2002), incidence-based measures of present and future costs attributable to smoking (Hodgson 1992), indirect costs of human capital lost from disability and premature deaths, and net social costs (Manning et al 1989;Herdman et al 1993;Barendregt et al 1997;Warner et al 1999). These studies have produced a wide range of estimates, depending on methodologies, assumptions incorporated into models, data sets used, and other methodologic issues.…”
Section: Smoking Attributable Economic Costs Economic Cost-of-illnessmentioning
confidence: 99%
“…One key issue is the comparison of the net versus the gross costs of smoking to society. Net costs would include consideration of the economic benefits of taxes, agricultural revenue, ancillary economic activity, and the "costs" of longer lives among nonsmokers that might offset the medical care costs of smokers or their lost productivity while they are alive (Warner 1987;Viscusi 1994;Barendregt et al 1997; U.S. Department of the Treasury 1998). A thorough discussion of the various methodologies and results is beyond the scope of this chapter, but Warner and colleagues (1999), Chaloupka and Warner (2000), Lightwood and colleagues (2000), and Max (2001) have provided extensive reviews of these issues.…”
Section: Smoking Attributable Economic Costs Economic Cost-of-illnessmentioning
confidence: 99%